In-vitro antibacterial activity of propolis extract against periodontopathogenic bacteria: a systematic review - Jéssica Gomes Alcoforado de Melo; Diego Moura Soares; Saulo Cabral dos Santos (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2024)
Objectives: The aim of this systematic review was to gather studies that use propolis extract to control antimicrobial activity and evaluate its activity in vitro against major periodontopathogens. Methods: A search of the PubMed/MEDLINE, Scielo, Lilacs, Science Direct, Cochrane, SCOPUS, Web of Science, and gray literature (Google Scholar and OpenGrey) databases was performed, complemented by a manual search. Articles meeting the following criteria were included: in-vitro studies that evaluated the action of propolis against at least one periodontopathogen. Results: The database search resulted in 1473 articles. After analysis of the titles and abstracts, 179 articles were duplicated, and 18 were selected for full-text screening, of which five were excluded. The manual search resulted in one article. This systematic review comprised 13 articles. Porphyromonas gingivalis appeared in all studies, and propolis showed an antibacterial effect, demonstrating the minimum inhibitory concentration. Conclusions: The propolis extract shows an effective antimicrobial activity on the periodontal pathogenic bacteria and may be a viable therapeutical option for the modulation of periodontitis. More studies are important to analyze the cytotoxic effects of different concentrations on gingival fibroblasts.